An Intelligent Remote Monitoring System for Total Knee Arthroplasty Patients. - Msayib, Yunus; Gaydecki, Patrick; Callaghan, Michael; Dale, Nicola; Ismail, Sheheera (Journal of Medical Systems, 2017)
For the first six weeks following total knee arthroplasty (TKA), a patient will attend an outpatient clinic typically seen twice weekly. Here, an exercise regime is performed and improvement assessed using a hand held goniometer that measures the maximum angle of knee flexion, an important metric of progress. Additionally a series of daily exercises is performed at home, recorded in a diary. This protocol has problems. Patients must attend the hospital with assistance since they are not permitted to drive for six weeks following the procedure; appointments are sometimes missed; there are occasionally not enough physiotherapy appointment available; furthermore, it is difficult to be sure that patients are compliant with their exercises at home. The economic and social costs are therefore significant both to the patient and the health service. We describe here an automatic system that performs the monitoring of knee flexion within a domestic environment rather than in a hospital setting. It comprises a master and slave sensor unit that attach using Velcro straps to the thigh and shin above and below the operation wound. The patient performs the prescribed knee exercises whilst wearing the device, during which time it measures and records the angles of knee flexion. The device utilises the Global System for Mobile Communications (GSM) infrastructure to transmit data through the Internet to a secure hospital-based server using an on-board GSM modem. The clinician is then able to view and interpret the information from any computer with internet access and the software. The system does not require the patient to possess a mobile telephone, a computer, or have internet access; the necessary communications technology is completely integrated into the device.